A crossover in the temperature behavior of the perpendicular upper critical magnetic field of layered superconductors and thin films - Gvozdikov, V. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
A mechanism which relates the upturn of the perpendicular upper critical magnetic field H^c2 (T) in layered superconductors and thin films with the structural inhomogeneity in the bulk of the sample, provided that the local critical temperature Tc* inside the inhomogeneity is higher than in the rest of the sample (Tc) is proposed. Within the Ginzburg-Landau approach an equation whic h describes two types of experimentally observed nonlinearities in H^c2 (T) near Tc for ISN (insulator-superconductor-normal metal) and NSN layer configurations, is found. In the NSN case a crossover from the linear branch H^c2 (T)µ (Tc-T), for fields H£ Hm, to the nonlinear branch with the upturn, if H > Hm, takes place. The crossover field Hm is inversely proportional to the local enhancement of the critical temperature (Tc*-Tc) and the distance R to the surface (the nearest surface, in case of a thin film). In the ISN case the upturn holds for H&ltHm, whereas for higher fields H^c2 (T) crosses over to the linear branch. In the ISI case the H^c2 (T) is a linear function.